2014
DOI: 10.3390/ijerph110404326
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of VOCs and Carbonyl Compounds Emission from Different Types of Wallpapers in Korea

Abstract: Emissions of volatile organic compounds (VOCs) and carbonyls from three types of commercially available wallpapers (i.e., PVC-coated, paper-backed, natural material-coated) in Korea were evaluated using a 20 L small chamber. A total of 332 products were tested for emission factors, frequencies of occurrence and composition ratios. Toluene and formaldehyde concentrations were below Korean standard values for all products; however, the total VOC (TVOC) concentrations exceeded current standards (4.0 mg/m2·h) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…In general, eco-friendly wallpaper contains less PVC and includes materials that are paper-backed or simply coated with natural material. One study reported that TVOCs and formaldehyde were less likely to be emitted from the paper-backed materials than materials coated with natural substances [14]. This difference between our finding and Yoo’s findings is probably because we used kenaf as the eco-friendly material, whereas Yoo et al used PP (polypropylene) resin.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In general, eco-friendly wallpaper contains less PVC and includes materials that are paper-backed or simply coated with natural material. One study reported that TVOCs and formaldehyde were less likely to be emitted from the paper-backed materials than materials coated with natural substances [14]. This difference between our finding and Yoo’s findings is probably because we used kenaf as the eco-friendly material, whereas Yoo et al used PP (polypropylene) resin.…”
Section: Discussioncontrasting
confidence: 85%
“…The old wallpaper was removed before the new one was installed. We used two kinds of wallpaper: EF wallpaper, which is manufactured using plant material such as kenaf, and PVC-coated wallpaper [14]. The PVC wallpaper looked similar to the EF wallpaper regarding color and texture selection.…”
Section: Methodsmentioning
confidence: 99%
“…Naphthalene is, indeed, primarily used as a chemical intermediate for phthalic anhydride and naphthalene sulphonate production, both involved in the industry manufacture of plasticizers, dyes and rubber formulations. Moreover, according to the existing literature, aromatic hydrocarbon release from polymeric materials (PVC, polyester) used as covering for interior materials such as wallpapers and flooring materials as well as polymeric items such as children toys may be mainly explained by taking into account the use of specific solvents in the manufacturing process such as toluene, ethylbenzene, isopropylbenzene and potential related impurities [4,19,29]. Estimated VOC emission rates from the investigated items on 'heating mode' are listed in Table 3.…”
Section: Test Chamber Experiments: Characterization Of Voc Emissions mentioning
confidence: 99%
“…Some building materials are high VOC emitters, such as solvent paints and adhesives and the coatings and coverings on walls, ceilings and floors [26,27]. Paints which are widely used in residential indoor environmental might contribute significantly to poor IAQ, especially as they are applied to large surfaces.…”
Section: Voc Emission From Building Productsmentioning
confidence: 99%